The Results of Gastric pH-metry in Patients with Extensive Burns - D. O. Vagner; K. M. Krylov; V. G. Verbitsky; M. I. Safoyev; I. V. Shlyk (Неотложная медицинская помощь, 2018)
Aim of study To study of the role of hydrochloric acid in the genesis of stress-induced gastric ulceration in patients with extensive burns.Material and methods The results of gastroscopy and endoscopic pH-metry of 30 young patients with extensive burns (19 male patients and 11 female patients). The acidity of the gastric contents was measured on day 1,7 and 14 after the trauma.Results It was found that the early period of burn disease was followed by the pH growth in the acid-producing area of the stomach to 3.8–4.2 (p=0.002–0.020). This indicated that extensive burns provoked a significant decrease of  hydrochloric acid production by parietal cells of the stomach. The restoration of the acid production occurred only 14 days after thermal injury and was not followed by the development of a hyperacid state. The frequency of erosive-ulcerative lesions detection in the gastric mucosa by the end of the first day after receiving burns was 83%, 87% on day 7, and 96% on day 14. In total, stress-induced lesions of the gastrointestinal mucosa were diagnosed in 26 of 30 patients with a shock-induced thermal injury. Consequently, in patients with burn shock the protective factors of the gastric mucosa were depressed so that a minimum amount of hydrochloric acid was sufficient to damage it.Conclusion Inhibition of acidogenic function is typical for patients with burn disease. Hydrochloric acid does not play a leading role in the genesis of stressinduced ulceration in patients with severe thermal trauma.